Tokenistic water and neoliberal sanitation in post-apartheid Durban. Issue 4 (2nd October 2019) - Bond, Patrick
ABSTRACT: Within the international water sector, Durban's municipal practitioners have been widely celebrated, for innovations in retail pricing, new product development, creative service delivery and community participation. However, in a society as divided as South Africa, with a high degree of neoliberal public policy influence from international sources, the myriad social, economic and environmental contradictions have reached deep into Durban's water and sanitation politics. Distant parts of the city were neglected when it came to 'uneconomic' water and sewage pipe extension. Tokenistic supplies of water were given to poor people, but in a manner that left them with one-third lower consumption levels. In surveys, the no-flush toilets were overwhelmingly rejected by hundreds of thousands of recipients. It is in the destruction of older water and sanitation policies, and the creation of new ones for poor and working-class black Durban residents, that adds new meaning to critical analysis of 'roll back' and 'roll-in' neoliberalisms.